2017
DOI: 10.1021/acs.chemmater.6b03952
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of Axial Si/Ge Nanowire Heterostructures Enabled by Trisilane

Abstract: Axial Si/Ge heterostructure nanowires, despite their promise in applications ranging from electronics to thermal transport, remain notoriously difficult to synthesize. Here, we grow axial Si/Ge heterostructures at low temperature using a Au catalyst with a combination of trisilane and digermane. This approach yields, as determined with detailed electron microscopy characterization, arrays of epitaxial Si/Ge nanowires with excellent morphologies and purely axial composition profiles. Our data indicates that het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(124 reference statements)
0
18
0
Order By: Relevance
“…Si/Ge and PbTe/PbSe [83,84]. Superlattice nanowires are grown using approaches that require changing the reactant gas in the VLS growth process as a function of time coupled with close control over growth conditions [85,86]. Measurements of thermal conductivity in Si/SiGe superlattice nanowires suggested that the thermal conductivity was significantly suppressed due to diffuse scattering of phonons at material interfaces as well as diffuse alloy scattering of phonons within the SiGe material layer [84].…”
Section: Heterogeneous Nanowires: the Impact Of Internal Surface Scatmentioning
confidence: 99%
“…Si/Ge and PbTe/PbSe [83,84]. Superlattice nanowires are grown using approaches that require changing the reactant gas in the VLS growth process as a function of time coupled with close control over growth conditions [85,86]. Measurements of thermal conductivity in Si/SiGe superlattice nanowires suggested that the thermal conductivity was significantly suppressed due to diffuse scattering of phonons at material interfaces as well as diffuse alloy scattering of phonons within the SiGe material layer [84].…”
Section: Heterogeneous Nanowires: the Impact Of Internal Surface Scatmentioning
confidence: 99%
“…The bottom-up growth of semiconductor nanowires through the vapor–liquid–solid (VLS) mechanism offers exquisite control over nanowire structure and composition , and thus functionality. Demonstrations of prototype transistors, photodetectors, solar cells, and biosensors, for example, highlight the promise of these materials for electronic, photonic, energy conversion, and medical applications. However, it remains difficult to produce nanowires in large quantities, especially those with the nanoscale compositional complexity required for the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…The bottom-up growth of semiconductor nanowires through the vapor-liquid-solid (VLS) mechanism offers exquisite control over nanowire structure and composition, 1-2 and thus functionality. [2][3][4][5][6] Demonstrations of prototype transistors, 7-10 photodetectors, [11][12][13] solar cells, [14][15][16][17] and biosensors [18][19][20][21] , for example, highlight the promise of these materials for electronic, photonic, energy conversion, and medical applications. However, it remains difficult to produce nanowires in large quantities, especially those with the nanoscale compositional complexity required for the above applications.…”
Section: Introductionmentioning
confidence: 99%